A critical review of competitiveness measurement in Northern Ireland. Issue 10 (3rd October 2019) - Birnie, Esmond; Johnston, Richard; Heery, Laura; Ramsey, Elaine
ABSTRACT: The measurement of regional competitiveness is an important and complex issue. Previous research has mostly considered national economies. However, indicators and measures identified at the national level may not apply well to regions. This paper contributes to knowledge by providing an analytical narrative of how the concept of the measurement of competitiveness has developed over time in Northern Ireland. The various stages in the development of measurements are critically evaluated. The region's chronic competitiveness shortfall is identified and possible explanations are indicated. The conclusions assess the most recent position regarding competitiveness measurement alongside a review of future research needs.